2024
DOI: 10.1094/phyto-01-24-0043-r
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Identification of Marker-Trait Associations Conferring Resistance to Scald from Globally Collected Barley Germplasm

Usman Ijaz,
Chenchen Zhao,
Sergey Shahbala
et al.

Abstract: Scald is one of the major economically important foliar diseases in barley, causing susceptible varieties up to 40% of yield loss. The identification of quantitative trait loci (QTL) and elite alleles that confer resistance to scald is imperative in reducing the threats to barley production. In this study, genome-wide association studies (GWAS) were conducted using a panel of 697 barley genotypes to identify QTL for scald resistance. Field experiments were conducted over three consecutive years. Among differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…For example, Rrs12 on chromosome 7H (Abbott et al 1991), Rrs14 on 1H (Garvin et al 1997) and Rrs15 on 7HL (Genger et al 2005) all originated from H. spontaneum, while Rrs16 Hb on 4HS originated from H. bulbosum (Pickering et al 2006). Although there are new reports of scald resistance, most recently on chromosomes 2H (Cope et al 2021), 5H (Coulter et al 2019;Zantinge et al 2019;Büttner et al 2020;Cope et al 2021) and 6H (Coulter et al 2019;Ijaz et al 2024), in some cases the resistance has been mapped to previously reported loci and it is unclear if the 'new' resistance is an allele of a currently known gene, or represents a closely linked gene. However, with the availability of an increasing number of genome assemblies (Jayakodi et al 2020(Jayakodi et al , 2024Mascher et al 2017Mascher et al , 2021 characterization of the various scald loci should be possible and allow a better understanding of the resistance located in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rrs12 on chromosome 7H (Abbott et al 1991), Rrs14 on 1H (Garvin et al 1997) and Rrs15 on 7HL (Genger et al 2005) all originated from H. spontaneum, while Rrs16 Hb on 4HS originated from H. bulbosum (Pickering et al 2006). Although there are new reports of scald resistance, most recently on chromosomes 2H (Cope et al 2021), 5H (Coulter et al 2019;Zantinge et al 2019;Büttner et al 2020;Cope et al 2021) and 6H (Coulter et al 2019;Ijaz et al 2024), in some cases the resistance has been mapped to previously reported loci and it is unclear if the 'new' resistance is an allele of a currently known gene, or represents a closely linked gene. However, with the availability of an increasing number of genome assemblies (Jayakodi et al 2020(Jayakodi et al , 2024Mascher et al 2017Mascher et al , 2021 characterization of the various scald loci should be possible and allow a better understanding of the resistance located in these regions.…”
Section: Introductionmentioning
confidence: 99%